Analysis of construction salt decomposition within walls of ceramic brick in the midtown tenement houses = Analiza rozkładu soli budowlanych w murach z cegły ceramicznej kamienic śródmiejskich - Szostak, Bartosz; Trochonowicz, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this paper is to introduce issues related to the corrosive effects of construction salts. Sequentially, one will discuss issues related to the distribution of salt in the wall, salinity sources and types of masonry material damage. There will also be presented the results of research conducted by the authors, which allowed determining the distribution of salinity in the walls depending on the depth and height of sampling.
Keywords: sole rozpuszczalne; cegła ceramiczna; mury z cegły ceramicznej; uszkodzenia murów; kamienice śródmiejskie; water soluble salts; ceramic brick; walls of ceramic brick; damaged walls; tenement